Գների ընդհանուր շարժի և գնագոյացման մի մեկնության շուրջ - Հարությունյան, Լիանա
Все видные представители экономической мысли, в той или иной степени обращались к теории стоимости, общего движения цен и ценообразования. В статье представлены взгляды армянского экономиста М.Бунятяна, которые по своей внутренней логике и методологии выявляют параллели с текущими экономическим процессам. В ходе анализа выявлено двоякое влияние изменения стоимости товара на общее движение цен. Представлен, выдвинутый Бунятяном принцип формирования субъективной ценности товара, предпринята попытка найти пределы восходящего движения цен и причины трансформации общего движения цен. All the prominent representatives of economic thought, past and present, have dealt to one degree or another with theories of value, the general movement of prices, pricing, and overproduction. The article presents the views of Armenian economist M. Buniatyan on the above-mentioned issues, which in their internal logic and methodology draw appeals to the current economic processes. During the analysis, the dual effect of the change in the value of goods on the general movement of prices, the principle of formation of the subjective value of goods put forward by Buniatyan was presented. An attempt was made to find the limits of the upward movement of prices and the reasons for the transformation of the pole of the general movement of prices.
Keywords: Տնտեսություն